Overexpression of FRAT1 Is Associated with Malignant Phenotype and Poor Prognosis in Human Gliomas. (2nd April 2015) - Guo, Geng; Zhong, Cheng-liang; Liu, Yang; Mao, Xing-gang; Zhang, Zheng; Jin, Ji; Liu, Jing; Yang, Liu; Mao, Jin-ming; Guo, Yu-hong; Zhao, Yuan-li
Abstract : Glioma is the most common malignancy of the central nervous system. Approximately 40 percent of intracranial tumors are diagnosed as gliomas. Difficulties in treatment are associated closely with the malignant phenotype, which is characterized by excessive proliferation, relentless invasion, and angiogenesis. Although the comprehensive treatment level of brain glioma is continuously progressing, the outcome of this malignancy has not been improved drastically. Therefore, the identification of new biomarkers for diagnosis and therapy of this malignancy is of significant scientific and clinical value. FRAT1 is a positive regulator of the Wnt/ β -catenin signaling pathway and is overexpressed in many human tumors. In the present study, we investigated the expression status of FRAT1 in 68 patients with human gliomas and its correlation with the pathologic grade, proliferation, invasion, angiogenesis, and prognostic significance. These findings suggest that FRAT1 may be an important factor in the tumorigenesis and progression of glioma and could be explored as a potential biomarker for pathological diagnosis, an indicator for prognosis, and a target for biological therapy of malignancy.